Failure analysis of pipe joint spiral wound gasket using finite element analysis (FEA) - Zainulariffin, Awang (2010)
This study describes the research and evaluation of the gaskets used in pipe systems. Referring to the title "Failure Analysis of Pipe Joint Gaskets Spiral wound”, this gasket is suitable for use in piping systems Spiral wound gasket designs are typically used in flat faced pipe flanges. They are also often used in pump applications with recessed flanges. Spiral wound gasket is an important component in the pipe system, this is because it functions as an additional component during the installation process pipe. It works to prevent the occurrence of leakage in the pipe connection system. These gaskets also have the distinct advantages that can withstand the high temperatures and pressures because the material used for manufacturing is gasket material that can withstand the high temperatures and pressures. Gasket is made up of several main sections, "inner ring, filler, and outer ring." Each section has its own features to prevent the leakage occurred. This matter to avoid the accident happened to the workers in this sector. The methodology of this project through the drawing spiral wound gasket using solid works and convert the drawing into Algor software. The mechanical test like tensile test, hardness test and metallurgical test also conduct in this project. All of the result has been discussed in this project and has been compared with other result. The mechanical test result has been record in this project, this is needed for the comparison between the analysis result. For the Algor analysis, it has been through the simulation to find stress and strain for the spiral wound gasket. For this analysis pressure (100 kN and 500 kN) has been applied in both directions. This is important to compare the value of the analysis to know the better type of gasket. From all analysis and result the gasket can be selected follow on the durability of the gasket from the result. Spiral wound gasket with inner ring has been recommended for using in the flanges system because it more durability than the spiral wound gasket without inner ring.